ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PADA KANTOR PERTANAHAN KABUPATEN KARANGANYAR (Studi Kasus pada Kantor Pertanahan Kabupaten Karanganyar) - Nisrina, Fildza Ainun; Suharno, Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this research is to analyze the significance of the influence of physical evidence, reliability, responsiveness, assurance and empathy towards the satisfaction of society on the Land Office Karanganyar Regency. This study used a survey method, the type of data the data used was qualitative and quantitative data, the source data used the primary data and secondary data. The population in this research community who came to the land Office Karanganyar Regency to take care of the exact number of certificate problem is unknown. The number of samples that used as many as 100 respondents, with sampling techniques using accidental sampling. Methods of data collection were used: questionnaire and documentation. Technique of data analysis used the test of validity, reliability test, test the assumptions of classical, and multiple linear regression analysis, t-test, F-test and coefficient of determination. The research results obtained the conclusion that there is a positive and significant influence of physical evidence against the satisfaction of the community. There is a positive and significant influence on reliability towards the satisfaction of the community. There is a positive and significant influence of responsiveness towards the satisfaction of the community. There is a positive and significant influence on security against the satisfaction of the community. There is a positive and significant influence of empathy towards the satisfaction of the community.